From Unequal Access To Differentiated Use: A Survey On Digital Inequality University Of Sulawesi Barat - Syaifuddin amir; Yasser shawqi abdur razeq; Darmawati.R; Sarimin Adang (International Journal of Education, Vocational and Social Science, 2022)
In exploring many of the divides that constitute the digital divide; this study examines the influence of gender in the Internet usage patterns of students of tertiary institutions in University of Sulawesi barat. Using stratified proportionate sampling, 377 respondents were chosen as the sample size of the study. Questionnaire was used to collect data from the respondents of the study which was subsequently analyzed using the SPSS software. Findings of the study reveal that the students are heavy Internet users (with usage rate of up to 98.13%). It also discovers several differences in the students‟ internet usage patterns. It reveals that male students (58.82%) use the Internet more than female students (41.18%). Findings of the study further indicate that female respondents mainly use the Internet for social networking while male students primarily use it for academic related purposes. It found that the gender differences in the students‟ Internet usage patterns are as a result of disparities in income, age, and educational attainment. The study recommends among other things, that a similar study be conducted on students of other tertiary institutions to see how the findings can be similar or different to this one